Comparison of work values of Malaysian youth in different contexts at school and university - Abdul Hamid, Jamaliah; Alby, Jeffrey Lawrence D'Silva (Asian Network for Scientific Information, 2015)
The social contexts of youth in different levels of the education system contain some differences. Youths in school are very much influenced by family orientations and peers towards work and work choices, whereas youths in colleges and universities gain wider exposure through socialization with fellow students and lecturers, administrators, external agents and through their involvement in a variety of campus activities. The exposure to different role sets and role models may engender differential influence on work values of students in schools and at universities. Although there are some researches of work values of adolescents, there are not many researches that compares youth work values across different age groups in school and university contextual settings. Yet this gap in knowledge is important if we are to examine the patterns of work values formation across different age levels and social-educational settings. This study aims to fill the gap in the knowledge of the formation of patterns of work values emerging amongst youths who are in the school setting, in comparison to those who have entered college and universities in Malaysia.